The gastronomy as an art and its role in the local economic development of a tourism destination: A literature review - Maria Manola; Stylianos X. Koufadakis (SPOUDAI - Journal of Economics and Business, 2020)
The purpose of this paper is to review recent research on the art of gastronomy and its contribution to local economic development as a result of the upgrading of gastronomic tourism. Hospitality and the culinary arts undoubtedly play a major role in influencing the experience of gastro-tourists who seek to enjoy unique taste sensations through the alternative gastronomic choices that are constantly being created globally. Gastronomy is not only the art of cooking and good eating; it has also been argued that is a complex experience that combines food with the cultural heritage of a tourist destination. Although there is a growing body of literature that recognizes the importance of tourism, it remains a major challenge to identify the contribution gastronomic tourism makes to economic development. Our study systematically reviews all the relevant recent literature on this topic, offering additional arguments for how the art of gastronomy can be utilized as a means of bolstering the economic prosperity of a host country.
Keywords: M1; L80; O1; 330; Gastronomic art; tourism; economic development